Digestibility and metabolizable energy of maize gluten feed for dogs as measured by two different techniques - Kawauchi, I. M.; Sakomura, N. K. [UNESP]; Vasconcellos, R. S.; de-Oliveira, L. D.; Gomes, M. O. S.; Loureiro, B. A.; Carciofi, A. C. [UNESP] (Elsevier B.V., 2011)
Maize gluten feed (MGF) is a co-product of wet milling of maize, and is composed of structures that remain after most starch, gluten and germ has been extracted from the grain. Although currently used in dog foods, its digestibility and energy values have not been documented. Two techniques were used to determine nutrient digestibility of MGF for dog foods. Both techniques used extruded diets fed to Beagle dogs, with six replicates per diet. The first study used a difference method in which 300 g/kg of a reference diet was replaced by MGF. Based on the difference method, the coefficient of total tract apparent digestibility (CTTAD) of MGF was 0.53 for dry matter (DM), 0.69 for crude protein (CP), 0.74 for fat, 0.99 for starch, and 0.55 for gross energy (GE). The calculated metabolizable energy (ME) of MGF was 7.99 MJ/kg (as-fed). The second study used a regression method and included a basal diet and a basal diet with 70, 140 and 210 g MGF/kg of diet (as a substitute for maize starch). Maize gluten feed inclusion resulted in a linear reduction of CTTAD of DM (R(2)=0.99; P<0.001), CP (R(2)=0.95; P=0.002), fat (R(2)=0.87; P=0.009). starch (R(2)=0.81; P<0.001), and GE (R(2)=0.99; P<0.001). Faecal production increased linearly from 56 g to 107 g/dog/d (R(2)=0.99; P<0.001), with a linear reduction of faecal DM (R(2)=0.99: P<0.001) and a linear increase in faecal lactic acid concentration (P<0.02). Both urine (R(2)=0.77; P=0.029) and faeces (R(2)=0.92: P=0.019) showed a linear reduction in pH. Results of ingredient MAD obtained by the regression and difference methods were close (6% or less of variation) for CP, fat, and starch, and also for ME content (1.4% higher for the difference method), but the two methods disagreed on calculated CTTAD of DM and organic matter. The high dietary fiber content of MGF (382 g/kg) may explain the low digestibility of this ingredient. Maize gluten feed could be a useful ingredient for formulations designed to have low energy or reduce the urine pH of dogs. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fiber; Maize; Short chain fatty acids; Starch